Il mondo sotto la superficie. L’ontologia liquida delle isole Belep (Kanaky Nuova Caledonia) - Lara Giordana (Archivio Antropologico Mediterraneo)
The recent literature on “marine sovereignty” encourages to consider the ways of management and governance of the Pacific Ocean from a new perspective, in order to face the ecological crisis and acknowledge the coexistence of different ontologies. In this paper I aim to convey the density and the poly-chrony that characterize the aquatic ontology of the Belema people, the inhabitants of the Belep Islands (Kanaky New Caledonia). For the Belema, the ocean is more than a surface to cross or the source of important economic resources. The ocean is a dense space: visible and invisible intertwine in its opaque depth; past and present, life and death mingle; human and non-human meet. The aquatic geography (a hydrography, punctuated by underwater villages and paths), the genealogies (in which the first ancestors are marine animals) and the continuities and correspondences between aquatic and terrestrial beings reveal the force of the ocean. It shapes the Belema society and contributes to making it a more-than-human society.